Local government reform - Barrington, T. J. (Statistical and Social Inquiry Society of Ireland, 1991)
I propose to put to you two main arguments that it is in the national interest at last to take seriously the Irish local government system. The first means taking a backward look to try to arrive at some quantitative and qualitative idea of the present state of that system as compared with some European norms. The second is to attempt a forward look, given the likely implications of the fact that, in the Taoiseach's words in the latest Programme for Economic and Social Progress, "we have fundamentally changed our approach to managing our affairs".
Symposium on Local Government Reform
Read before the Society, 21 March 1991
Keywords: Local government; Participatory democracy; 314.15